Novel training and other strategies for sport performance at the 2011 ACSM Annual Meeting - Hopkins, W. G.; Martin, D. T.; Knight, M. C. (Sportscience, 2011)
The annual conference of the American College of Sports Medicine was note-worthy for its variety of novel performance-enhancing strategies based on training and post-activation potentiation. Denver Highlights with Dave Martin: pacing, US Olympic Training Center, altitude, central governor, models, US military, energy balance, networking. Take-home Messages from Marty Knight: creatine, footwear injuries, barefoot running, Vitamin D, genetic testing, older adults, evidencebased education, alternative learning. Abstracting No Effect by Will Hopkins: The meaning of non-significance in underpowered studies is misunderstood. Acute Effects: Compression socks, ionized compression gar-ments, ibuprofen, warm-ups with post-activation potentiation, hyperoxemia, cold-water immersion. Nutrition: acute and chronic antioxidants, iron, bananas, coconut water, chicken essence and ginseng, fructose:maltodextrin ratio, caffeine, charge-stabilized nanostructures, leucine, creatine, bicarbonate, sodium lactate, combinations of ergogenics, pseudoephedrine, beetroot. Tests, Technology and Modeling: poorly designed cross-sectional studies, new running shoe, modeling power output, oxygen cost. Training: functional vs traditional resistance, linear vs undulating periodized resistance, unstable vs stable sur-face resistance, hypoxia vs normoxia resistance, effects of step frequency on economy, traditional strength on endurance, underweight softball bats, core strength on endurance, snorkel on endurance, traditional altitude on competitions. KEYWORDS: elite athletes, ergogenic aids, nutrition, tests, training.